Pemeringkatan Calon Penerima Beasiswa SD Negeri 3 Wadas, Kendal Menggunakan Metode AHP-Copras - Perdana, Dimas Satria; Wibisono , Setyawan (MEANS (Media Informasi Analisa dan Sistem), 2024)
The main obstacle in the selection process for scholarship recipients at SD Negeri 3 Wadas is that selection is only based on one or two criteria without considering other relevant factors, such as family economic conditions, academic achievement and student age, which can lead to uneven and uneven distribution of scholarships. right on target. This research aims to develop a ranking model for prospective scholarship recipients at SD Negeri 3 Wadas using the criteria of family income, number of family members, age of students, average grades, and income per person. The final results of the ranking show that prospective scholarship recipients with a small income per person, small family income, large family size will make prospective scholarship recipients the best choice, this is because the criteria for income per person and family income have the highest weight. On the other hand, scholarship recipients with a large income per person, a large family income and a small family size will be the lowest choice in the ranking list